Early BHs: simulations and observations. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Cappelluti, Nico; Di-Matteo, Tiziana; Schawinski, Kevin; Fragos, Tassos
Abstract: We report recent investigations in the field of Early Black Holes. We summarize recent theoretical and observational efforts to understand how Black Holes formed and eventually evolved into Super Massive Black Holes at high-z. This paper makes use of state of the art computer simulations and multiwavelength surveys. Although non conclusive, we present results and hypothesis that pose exciting challenges to modern astrophysics and to future facilities.